The Meaning Of Financial Transparency In Toraja Church Services: A Phenomenological Study Of Council Practices In The Perindingan Congregation Of The Klasis Sillanan - Yohanis Lotong Ta’dung; Marinus Ronal (LP2M IAIN Palopo, 2025)
This study explores the meaning of financial transparency within the church services of the Perindingan Congregation, Klasis Sillanan, Toraja Church. Using a phenomenological approach, this research seeks to uncover the lived experiences, perceptions, and interpretations of church council members regarding the practice of financial management and reporting. Data were collected through in-depth interviews, observations, and documentation to capture the essence of transparency as experienced in daily church activities. The findings reveal that financial transparency is not merely understood as accountability in managing church funds but also as a reflection of spiritual integrity, collective trust, and social harmony within the congregation. The study highlights that transparent financial practices strengthen the congregation’s faith in leadership, foster participation, and sustain the moral foundation of church governance. This research contributes to the broader understanding of how ethical and spiritual values shape financial accountability in faith-based institutions.